Obsessive-compulsive, harm-avoidance and persistence tendencies in patients with gambling, gaming, compulsive sexual behavior and compulsive buying-shopping disorders/concerns - Mestre-Bach, Gemma; Granero, Roser; Fernández-Aranda, Fernando; Potenza, Marc N.; Jiménez-Murcia, Susana (Addictive Behaviors, 2023)
Background and aims: There is a growing interest in determining the specific role of obsessive–compulsive features in different behavioral addictions. However, more studies comparing sizable clinical populations with different addictions are needed.Therefore, a main aim of the present study was to explore the presence of obsessive–compulsive features among people with different behavioral addictions (gambling disorder, internet gaming disorder, compulsive sexual behavior disorder and compulsive buying-shopping concerns). Through a clustering procedure, the existence of empirical clusters among treatment-seeking patients based on obsessive–compulsive measures was explored. Materials and methods: The Symptom Checklist-Revised, and the Temperament and Character Inventory-Revised were obtained from 4,010 treatment-seeking patients. Obsessive-compulsive features were measured with the obsessive–compulsive subscale of the Symptom Checklist-Revised and the harm avoidance and persistence dimensions of the Temperament and Character Inventory-Revised. Cluster analysis was applied to explore the existence of empirical groups based on obsessive–compulsive features. Results: Patients with compulsive sexual behavior disorder and compulsive buying-shopping disorder reported the highest scores on the obsessive–compulsive subscale, while patients with gambling disorder showed the lowest scores on harm avoidance, and patients with internet gaming disorder the lowest scores on persistence. Two mutually exclusive clusters were identified. Cluster 1 exhibited a more maladaptive psychopathological and personality profile than cluster. Discussion and Conclusions: These results provide new evidence regarding obsessive–compulsive features in specific behavioral addictions. Therapeutic approaches should consider that different addictions may present distinct levels of obsessive–compulsive features.
Keywords: addictive behaviors; compulsive sexual behaviors; gambling; impulsive behaviors; obsessive-compulsive behaviors; video games; Scopus; JCR